ФИТОЦЕНОТИЧЕСКОЕ СОСТОЯНИЕ БЕЛОЗЕМЕЛЬНОПОЛЫННО-КЕЙРЕУКОВО-САКСАУЛОВОЙ ПАСТБИЩНОЙ РАЗНОСТИ НА КАРАКАЛПАКСКОМ УСТЮРТЕ - Тамамбетова, Ш.Б. (SCIENCE and SOCIETY, 2025)
The article presents data on the study of the yield of feed mass, the nutritional value of feed, landscape plant species in the pastures of the Karakalpak part of Ustyurt. The phytocoenotic state of Haloxylon ammodendron, Salsola orientalis, Artemisia terrae-albae of pasture difference (PD) from Haloxylon pasture type was revealed. As a result of the conducted research, their area, the nature of the soil cover, the percentage of projective coverage, landscape plant species, the yield of feed mass, the recommended seasonality of the use of pasture differences were determined. It was determined that the seasonal yield of the feed mass of Haloxylon ammodendron, Salsola orientalis, Artemisia terrae-albae ranges from 3,9 to 7,9 c/ha, the maximum value falls on the autumn and winter period, the dominants reach their maximum increase in this period. According to estimates of the yield of the eaten part (c/ha), this type is recommended to be used as a year-round pasture.
Keywords: formation; massif; Haloxylon ammodendron; Artemisia terrae-albae; Ustyurt Plateau; pastures; landscape; complex